2004
DOI: 10.1603/0022-0493(2004)097[1112:iorwah]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Russian Wheat Aphid (Homoptera: Aphididae) Populations Virulent to the <I>Dn4</I> Resistance Gene

Abstract: The Russian wheat aphid, Diuraphis noxia (Mordvilko), is a serious worldwide pest of wheat and barley. Russian wheat aphid populations from Hungary, Russia, and Syria have previously been identified as virulent to D. noxia (Dn) 4, the gene in all Russian wheat aphid-resistant cultivars produced in Colorado. However, the virulence of Russian wheat aphid populations from central Europe, North Africa, and South America to existing Dn genes has not been assessed. Experiments with plants containing several differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The usefulness of the resistant genotypes we found, especially those with resistance to R. padi and S. avenae, will be largely determined by the genetic variation in aphid populations. It is well known that aphid virulence can vary in different geographic areas, as demonstrated for the Russian wheat aphid (Haley et al 2004;Smith et al 2004a;Weiland et al 2008). Several unique S. graminum biotypes in the USA differ in virulence patterns to resistant cultivars (Burd and Porter 2006), and were present before resistant cultivars were grown (Porter et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The usefulness of the resistant genotypes we found, especially those with resistance to R. padi and S. avenae, will be largely determined by the genetic variation in aphid populations. It is well known that aphid virulence can vary in different geographic areas, as demonstrated for the Russian wheat aphid (Haley et al 2004;Smith et al 2004a;Weiland et al 2008). Several unique S. graminum biotypes in the USA differ in virulence patterns to resistant cultivars (Burd and Porter 2006), and were present before resistant cultivars were grown (Porter et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Aphid resistance can be conferred polygenically or monogenically and the genes are often located in resistance gene clusters within specifi c chromosomal regions (Dogimont et al, 2010). To date, 12 named RWA resistance genes (Dn genes) have been identifi ed: Dn1 and Dn2 (Du Toit, 1987, 1988, 1989, dn3 and Dn4 (Nkongolo et al, 1991a, b), Dn5 (Marais and Du Toit, 1993), Dn6 (Saidi and Quick, 1996), Dn7 (Marais et al, 1994), Dn8, Dn9, and Dnx (Harvey and Martin, 1990;Liu et al, 2001), Dny (Smith et al, 2004), and resistance conferred by the cereal introduction CI 2401 (consisting of two R genes, one allelic to Dn4 and the other diff erent from known Dn genes) (Collins et al, 2005;Dong et al, 1997;Voothuluru et al, 2006). Chromosomal locations of many of these genes have been identifi ed.…”
mentioning
confidence: 99%
“…The most recent study conducted by Liu et al (2005) concluded that Dn1, Dn2, Dn5, Dn6, and Dnx were either allelic at the same locus or located in a Dn gene cluster and tightly linked to each other and to simple sequence repeat (SSR) marker Xgwm111. Despite the identifi cation and characterization of these genes, all except Dn7 are ineff ective against the most virulent biotype, RWA2 (Collins et al, 2005;Haley et al, 2004;Peng et al, 2007;Smith et al, 2004).…”
mentioning
confidence: 99%
“…Basky (2003) reported that wheat cultivars resistant to RWA isolates of South Africa were susceptible to Hungarian RWA populations, indicating that RWA biotypes are different between the two countries. Russian wheat aphid populations from Central Europe, North Africa, and South America also produced different virulence profiles to a set of cultivars carrying different known genes (Smith et al, 2004). Moreover, a sexually reproduced RWA population with a high degree of biotypic diversity has been discovered in the high plateau region of western Colorado (Puterka et al, 2012).…”
Section: Crop Sciencementioning
confidence: 99%